2022
DOI: 10.1097/iae.0000000000003530
|View full text |Cite
|
Sign up to set email alerts
|

Baseline Sattler Layer–choriocapillaris Complex Thickness Cutoffs Associated With Age-Related Macular Degeneration Progression

Abstract: To assess the relationship between choroidal overall and sublayer thickness and age-related macular degeneration (AMD) stage progression.Methods: A prospective, observational case series was performed. Two hundred and sixty-two eyes of 262 patients with different stages of AMD were imaged by optical coherence tomography. Age-related macular degeneration stage, choroidal thickness, Sattler layer-choriocapillaris complex thickness (SLCCT), and Haller layer thickness were determined at the baseline visit, at a 1-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 28 publications
1
3
0
Order By: Relevance
“…Recently, an association between CVI and GA growth has been reported 10 . Our research group also found that choroidal thinning takes place predominantly in the Sattler layer-choriocapillaris complex 11 .…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…Recently, an association between CVI and GA growth has been reported 10 . Our research group also found that choroidal thinning takes place predominantly in the Sattler layer-choriocapillaris complex 11 .…”
Section: Discussionsupporting
confidence: 68%
“…Subfoveal and mean choroidal thickness (CT), Haller layer thickness (HLT) and Sattler layer-choriocapillaris complex thicknesses (SLCCT), and choroidal vascularity index (CVI) at baseline and at the end of the follow-up were measured on OCT B-scans centered on the fovea, in accordance with the current literature 11 , 20 , 21 . Large choroidal vessels defined the Haller layer, whereas SLCCT was defined as the distance between the lower border of the retinal pigment epithelium–Bruch complex and the upper border of the Haller layer, as previously reported 11 .…”
Section: Methodsmentioning
confidence: 81%
See 1 more Smart Citation
“…Choroidal thickness is thinner in patients with AMD than in those without retinal pathology [ 86 ]. In one study, reduction in the choriocapillaris complex thickness was significantly associated with AMD progression over 5 years of follow-up ( p < 0.001): a thickness of < 10.5 µm was associated with a high probability of progression, whereas a thickness of > 10.5 but < 20.5 µm was associated with moderate probability [ 87 ]. However, the relationship between choroidal thickness and AMD status is affected by several other factors, such as axial length, age, and possibly the presence of RPD, which complicates the reported associations [ 86 , 88 ].…”
Section: Structural Biomarkersmentioning
confidence: 99%